Combination Cisplatin‐Epirubicin‐Paclitaxel Therapy for Metastatic Extramammary Paget's Disease. (7th March 2019) - Hirai, Ikuko; Tanese, Keiji; Nakamura, Yoshio; Ishii, Maki; Kawakami, Yutaka; Funakoshi, Takeru
Abstract: Extramammary Paget's disease (EMPD) is a rare cutaneous adenocarcinoma that clinicopathologically resembles breast cancer. The prognosis of metastatic EMPD is poor. Although several chemotherapies have been tried, the effects are temporary; better drugs and combinations are required. In the present study, we retrospectively analyze the efficacy and safety of combination of cisplatin, epirubicin, and paclitaxel in five metastatic EMPD cases. The efficacy was better than that for previously reported regimens: 80% partial responses, including two patients who were refractory to taxane‐ and/or platinum‐based regimens. In terms of safety, four patients who were able to continue treatment exhibited acceptable tolerability. This is the first regimen to combine taxane and anthracycline. When treating breast cancer, anthracycline is regarded as the key cytotoxic agent, and anthracycline in combination with taxane constitutes a key chemotherapeutic regimen. Given our results, we speculate both drugs are critical chemotherapeutic agents for the treatment of metastatic EMPD. Abstract : This brief communication analyzes the long‐term efficacy and safety of a modified PET regimen in five cases of metastatic extramammary Paget's disease.